Comparative evaluation of cell viability immediately after osteotomy for implants with drills and piezosurgery: Immunohistochemistry analysis - Pereira, Cassiano Costa Silva [UNESP]; De Souza Batista, Fábio Roberto [UNESP]; Jacob, Ricardo Garcia Mureb [UNESP]; Nogueira, Lamis Meorin [UNESP]; De Souza Carvalho, Abrahão Cavalcante Gomes [UNESP]; Gealh, Walter Cristiano [UNESP]; Garcia-Júnior, Idelmo Rangel [UNESP]; Okamoto, Roberta [UNESP] (Wolters Kluwer, 2018)
Objective: To evaluate the effect of reusing drills and piezosurgery tips during implant osteotomy on immediate bone cell viability through immunohistochemical analysis. Materials and Methods: Six male rabbits were divided into 2 groups and then divided into 5 subgroups-correspond to drills and tips used 10, 20, 30, 40, and 50 times, respectively. All animals received 10 osteotomies in each tibia, by use of the classic drilling procedure in one group (G1) and the piezosurgery device in the other group (G2). For immunohistochemical technique were utilized the osteoprotegerin, RANKL, osteocalcin, and caspase 3. Control procedures were performed by omitting the primary antibodies (negative control). Results: Bone formation and resorption responses presented in more intense way during the piezosurgery. The expression of osteocalcin had become quite intense in piezosurgery groups, but with reduced immunostaining from the 30th osteotomy. The caspase 3 showed the viability of the osteoblast from the 20th osteotomy with piezosurgery and remained constant until the 50th. Conclusion: Piezosurgery provides greater osteoblastic cell viability than the system of conventional drilling. Clinical Relevance: This study will provide data so that the authors can recycle the drills and tips for implant placement, thus enabling a better cell viability for osseointegration.
Keywords: Cell surviving; Dental implants; Immunohistochemistry; Osteoblasts; Osteotomy